Seasonal Variation in the Larval Population of Brinjal Shoot and Fruit Borer Leucinodes orbonalis Guenee with Respect to Different Ecological Parameters - Nayak, U. S.; Baral, K.; Mandal, P.; Chatterjee, S. (International Journal of Bio-resource and Stress Management, 2023)
The study on the variation in larval population of brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis Guene was carried out during rainy, winter and summer seasons of 2009-10 and 2010-11 at Keonjhar district of Odisha under field conditions. During rainy season, the larval infestation initiated in last week of June and increased progressively with two distinct peak level. The first peak was observed during 2nd and 3rd week of August and the second one was attained during 3rd week of September and 1st week of October, respectively in 2009 and 2010. In the winter season, the larvae of BSFB appeared for the first time 4th week of October with two subsequent peak population level during the crop growth period. The initial peak was attained during 3rd and 1st week of December for 2009-10 and 2010-11, respectively and the subsequent peak was observed at 3rd week of February for both the years of study. In contrast, in the summer season the larvae of BSFB first appeared on 4th week of January during both the years of trial and registered an increasing trend to attain two well defined peaks during the crop growth period. The first peak larval population was observed during 1st fortnight of April followed by the second peak during 3rd week of May. Among the ecological parameters temperature exerted positive and relative humidity had negative influence on the pattern of larval population variation. These two weather variable had maximum contribution towards the variation in larval intensity.